Child labor and its determinants: An empirical test of the luxury axiom-cum the wealth paradox theory - Kidanemariam Gebregziabher; Muuz Hadush; Kebede Abrha (Cogent Economics & Finance, 2023)
The paper was motivated to test whether the high child labor prevalence observed in Ethiopia is explained by the poverty (luxury) hypothesis or wealth paradox theories. The data for this study is the Young Lives project, consisting of 1803 children units (a total of 7212 children in four rounds). Major determinants of child labor: household characteristics, shocks, poverty or wealth proxy indicators, and area and time fixed effect variables are controlled. The study employs a Feasible generalized least squares (FGLS) econometric technique to estimate the causal relationship between child labor; household characteristics, poverty, and wealth indicator variables. Both drought and income losses were found to be positive and significant almost across all specifications. Resource or asset ownership indicators, such as land, access to credit, and TLU) were found to be positively related to child labor, consistent with the wealth paradox. However, the wealth index, except in the two quartiles found to be negative and significant at 1 percent, consistent with the luxury axiom. One more result that is interesting is the significant differences between boys and girls in the type of tasks children engaged in. Girls' dominance in household chores and boys in economic activity. Moreover, the current high level of child labor participation rate of 45 percent is very alarming. Finally, the household head's educational status also has a strong negative impact on child labor. In view of, the moral obligation of societies and government; future economic benefit of investing in children, policy be directed towards pro-poor development programs especially targeting children's welfare, promoting adult education, and introducing agricultural insurance schemes to reduce the extent and intensity of child labor.
Keywords: F66; J01; J08; J48; 330; child labor; feasible generalized least squares; luxury axiom; wealth paradox